2010
DOI: 10.1002/jcb.22878
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of differentially expressed genes in goose hepatocytes exposed to free fatty acid

Abstract: The overaccumulation of triglycerides in hepatocytes induces hepatic steatosis; however, little is known about the mechanism of goose hepatic steatosis. The aim of this study was to define an experimental model of hepatocellular steatosis with TG overaccumulation and minimal cytotoxicity, using a mixture of various proportions of oleate and palmitate free fatty acids (FFAs) to induce fat-overloading, then using suppressive subtractive hybridization and a quantitative PCR approach to identify genes with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Positive selection analysis identified a series of PSGs enriched in lipid metabolism and RNA processing. Involved genes such as APOB participate in de novo synthesis of fatty acids and were associated with goose hepatic steatosis 38 . Cholesteryl ester transfer protein ( CETP ) has been shown to play a role in liver lipid metabolism 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Positive selection analysis identified a series of PSGs enriched in lipid metabolism and RNA processing. Involved genes such as APOB participate in de novo synthesis of fatty acids and were associated with goose hepatic steatosis 38 . Cholesteryl ester transfer protein ( CETP ) has been shown to play a role in liver lipid metabolism 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, goose primary hepatocytes were treated with higher dosages (25 or 50 mM) of glucose due to the following consideration: (1) The acute effect of strong stimulation (high glucose) may better mimic the chronic effect of hyperglycemia on the hepatocytes in goose liver than that of weak stimulation (low glucose as in blood); (2) when insulin resistance occurs in goose fatty liver, glucose transporter may pump a large amount of glucose into the hepatocytes in the liver in addition to the diffusion of glucose, which may lead to intracellular glucose level much higher than blood glucose level; (3) Treatment with high level of glucose was previously reported by some in vitro studies [55]. In regard to treatments with 0.25/0.5 mM fatty acids and 100/200 nM insulin, previous studies were also referenced, including those showing serum-free fatty acids were above 0.5 mM in mammalian animals [56][57][58], as well as those using the same or even higher dosages for in vitro studies with mammalian cells and avian cells [55,59,60]. These in vitro studies indicated that the expression of Fads genes was differentially regulated by these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 activity assay HOK cells were lysed by using a lysis buffer (1% Triton X-100, 1 mM DTT, 25 mM Hepes, 115 mM NaCl, 1 mM KH 2 PO 4 , 4 mM KCl, and 1 ml/ml protease inhibitor cocktail) on ice for 10 min, then collected and centrifuged to have the supernatants as cell lysate. The caspase-3 activity in cell lysates was evaluated by using a specific fluorogenic caspase substrate Ac-DEVD-AFC (BioVision, Milpitas, CA, USA) and measured at Ex.360/Em.530 on a plate reader as previously described (33,34).…”
Section: Tunel Stainingmentioning
confidence: 99%